(untitled) (Olhares, 2020)
case study of “o teatro que vem” (“the theatre that comes”), a research project carried at escola superior de artes célia helena (esch, são paulo), in 2020. the project joined graduate students of two disciplines (history of brazilian theatre i and history of theatre performance ii) of the theatre programme, to produce a podcast interviewing individual artists and groups who, from the perspective of our young researchers, best represented now the paths that theatre in brazil should follow in the future. particular attention is given to the consequences of the covid-19 pandemic to the work dynamics developed at esch from march 2020 onwards.